2008
DOI: 10.1590/s1413-80502008000400006
|View full text |Cite
|
Sign up to set email alerts
|

Dominância fiscal ou dominância monetária no Brasil? Uma análise de causalidade

Abstract: ¤ resumoO objetivo deste estudo é verificar se existe dominância fiscal ou monetária na economia brasileira no período pós-Plano Real. Investiga-se a relação de equilíbrio de longo prazo e a causalidade de Granger bivariada e multivariada entre as variáveis taxa nominal de juros, relação dívida/PIB, relação superávit primário/PIB, taxa real de câmbio e o prêmio de risco. Os resultados sugerem que a economia brasileira encontra-se sob regime de dominância monetária, segundo as definições propostas por Sargent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
2
7
0
3
Order By: Relevance
“…They concluded that public spending did not cause GDP growth, it is mostly a consequence of economic growth, supporting Wagner´s Law. Gadelha & Divino (2008) investigated whether there is monetary dominance or fiscal dominance 4 in Brazil. They applied models of multivariate and bivariate Granger causality, with monthly data over January 1995 and December 2005.…”
Section: Studies Applied To Brazilmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that public spending did not cause GDP growth, it is mostly a consequence of economic growth, supporting Wagner´s Law. Gadelha & Divino (2008) investigated whether there is monetary dominance or fiscal dominance 4 in Brazil. They applied models of multivariate and bivariate Granger causality, with monthly data over January 1995 and December 2005.…”
Section: Studies Applied To Brazilmentioning
confidence: 99%
“…The studies applied to Brazil did not focused on the relationship between public debt and growth, most of them emphasised the relation between government expenditures and revenues or government expenditures and growth 5 .Therefore, this study differentiates from empirical literature applied to Brazil by analysing the relation between government debt and GDP. Moreover, aiming to find a more complete relationship we included the variables used by Gadelha & Divino (2008), that are interest rate, inflation rate, exchange rate, primary surplus and Embi+ 6 , since these variables are also important for the changes in public debt and economic growth.…”
Section: Studies Applied To Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…Esses fatores são apontados como origem da vulnerabilidade no longo prazo e que inviabilizam o ajuste fiscal (GADELHA; DIVINO, 2008;FARAH, 2008;KLEIN, 2010;NEDUZIAK, 2013).…”
Section: Esforço Fiscalunclassified
“…Os testes permitiram aos autores testar a definição de dominância monetária proposta por Sargent e Wallace (1981) na qual "a existência de causalidade unidirecional do superávit primário para a dívida pública é consistente com um regime de dominância monetá-ria, ao passo que uma causalidade unidirecional em sentido oposto, da dívida pública para o superávit primário, define um regime de dominância fiscal" (GADELHA; DIVINO, 2008), além de testar a existência da transmissão entre variáveis fiscais e monetárias segundo o trabalho de Blanchard (2004).…”
Section: Literatura Empírica Brasileiraunclassified